Maternal nutritional restriction during late gestation impairs development of the reproductive organs in both male and female lambs - Hoffmann, Federico (2018)
Maternal nutritional restrictions during late gestation could lead to fetal hypoglycemia. Glucose levels in the fetal sheep regulate circulating insulin-like growth factor 1 (IGF1) levels, which stimulate cell proliferation and differentiation of reproductive organs after binding to its own receptor or estrogen receptors. The objective of this study was to determine the effects of subnutrition of ewes during the last trimester of gestation on the serum glucose/IGF1 levels and development of reproductive organs in their lambs. Pregnant ewes carrying singletons were randomly assigned to restricted (R ewes, n = 8) or control (C ewes, n = 8) groups (4 lambs of each gender/group) and fed with 50% or 100% of metabolic energy requirements from ∼100 days of gestation to term (∼147 days), respectively. Blood samples from lambs were taken on the first day after born and once at week for serum glucose and IGF1 determination. Lambs were euthanatized at 2 months of age, reproductive organs were weighted and tissue samples were collected from them for histology and to measure mRNA expression of IGF1 and its receptor (IGF1R) by qRT-PCR. Pre-partum glucose levels in R ewes were significantly lower compared to C ewes (p <.05). Compared to lambs born from C ewes, lambs born from R ewes showed lower serum levels of glucose and IGF1 during the first week of age (p <.05). At 2 month of age, these lambs had significant lower uterine and testicular weight and lower ovarian, uterine and testicular mRNA expressions of IGF1 and its receptor (p <.05). Histological findings showed that diameter of secondary and tertiary follicles in ovaries and number of endometrial glands in uterus of females, or number of Sertoli cells and seminiferous tubules and diameter, perimeter and tubular area in testicles of males were significantly lower in lambs born from R ewes compared to the respective organs of lambs born from the C ewes (p <.05). In conclusion, these results demonstrate that maternal subnutrition during late gestation affects IGF1 levels during fetal life and impairs reproductive development in the neonatal lamb, which could have permanent negative consequences in the future reproductive performance of the offspring.